Glyphosate Resistance in Perennial Ryegrass (Lolium perenne L.) is Associated with a Fitness Penalty. Issue 1 (March 2016) - Yanniccari, Marcos; Vila-Aiub, Martín; Istilart, Carolina; Acciaresi, Horacio; Castro, Ana M.
Abstract : The net selection effect of herbicides on herbicide-resistance traits in weeds is conditioned by the fitness benefits and costs associated with resistance alleles. Fitness costs play an important evolutionary role preventing the fixation of adaptive alleles and contributing to the maintenance of genetic polymorphisms within populations. Glyphosate is widely used in world agriculture, which has led to the evolution of widespread glyphosate resistance in many weed species. The fitness of glyphosate-resistant and -susceptible perennial ryegrass plants selected from within a single population were studied in two field experiments conducted during 2011 and 2012 under different soil water availability. Glyphosate-resistant plants showed a reduction in height of 12 and 16%, leaf blade area of 16 and 33%, shoot biomass of 45 and 55%, seed number of 33 and 53%, and total seed mass of 16 and 5% compared to glyphosate-susceptible plants in 2011 and 2012, respectively. The reduction in seed number per plant resulted in a 40% fitness cost associated with the glyphosate-resistance trait in perennial ryegrass. Fitness costs of glyphosate-resistant plants were expressed under both conditions of water availability. These results could be useful for designing management strategies and exploiting the reduced glyphosate-resistant perennial ryegrass fitness in the absence of glyphosate selection.